204k views
19 votes
Match the information on the left with the appropriate equation on the right.

An equation perpendicular to y = - 3x + 1 through the point
(3,-2)

An equation through the point ( - 2, 3) and parallel to
y = - 3x - 1

Match the information on the left with the appropriate equation on the right. An equation-example-1
User John Prado
by
5.6k points

2 Answers

5 votes
3)7?,79 that the same name of this game I
User Kit Ho
by
5.1k points
3 votes

To find the equation perpendicular to y = -3x + 1 through the point (3, -2), the slope of the line is 1/3. Therefore, the equation would be y = 1/3x - 3. For an equation through the point (-2, 3) and parallel to y = -3x - 1, the equation would be y = -3x - 3.

To find an equation perpendicular to y = -3x + 1 through the point (3, -2), we first need to find the slope of the given equation.

The slope of the given equation is -3.

The slope of a perpendicular line is the negative reciprocal of the original slope.

Therefore, the slope of the perpendicular line is 1/3.

Using the point-slope form of an equation, we can plug in the values: y - y1 = m(x - x1).

Substituting (3, -2) and slope 1/3, we get y - (-2) = 1/3(x - 3). Simplifying further, we get y + 2 = 1/3x - 1.

Rearranging the equation, we get y = 1/3x - 3, which is the equation perpendicular to y = -3x + 1 through the point (3, -2).

For an equation through the point (-2, 3) and parallel to y = -3x - 1, the slope of the parallel line will be the same as the slope of y = -3x - 1, which is -3.

Using the point-slope form again, we substitute (-2, 3) and slope -3 into the equation.

This gives us y - 3 = -3(x - (-2)).

Simplifying further, we get y - 3 = -3(x + 2).

Rearranging the equation, we get y = -3x - 3, which is the equation through the point (-2, 3) and parallel to y = -3x - 1.

User MarkHu
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.